Revolutions happen like refrains in a song - Deocampo, Nick (Nick Deocampo, 2007)
This documentary is both intensely personal and political. Deocampo introduces himself as a witness to the revolution: the first part of the film is a personal documentation of the downfall of the Marcos regime. The filmmaker then ranges over his own childhood, via still photographs and home movies, during the years of the Marcos regime. He also reprises his films Oliver and Children of the Regime, the former focused on a male prostitute, the latter on investigation of child prostitution. This is an insistent voice from within the upheavals in the Philippines of the eighties.